Bioactive Glass Foam Scaffolds are Remodelled by Osteoclasts and Support the Formation of Mineralized Matrix and Vascular Networks In Vitro. Issue 3 (22nd October 2012) - Midha, Swati; van den Bergh, Wouter; Kim, Taek B.; Lee, Peter D.; Jones, Julian R.; Mitchell, Christopher A.
Abstract Remodelling of scaffolds and new bone formation is critical for effective bone regeneration. Herein is reported the first demonstration of resorption pits due to osteoclast activity on the surface of sol–gel bioactive glass foam scaffolds. Bioactive glass foam scaffolds are known to have osteogenic potential and suitable pore networks for bone regeneration. Degradation of the scaffolds is known to be initially solution mediated, but for effective bone regeneration, remodelling of the scaffold by osteoclasts and vascularisation of the scaffold is necessary. The culture of C7 macrophages on a bioactive glass scaffold induces the cells to differentiate into (TRAP+ve) osteoclasts. They then form distinctive resorption pits within 3 weeks, while MC3T3‐E1 pre‐osteoblasts deposit mineralized osteoid on their surfaces in co‐culture. The scaffolds are of the 70S30C (70 mol% SiO2, 30 mol% CaO) composition, with modal pore and interconnect diameters of 373 μm and 172 μm respectively (quantified by X‐ray micro‐tomography and 3D image analysis). The release of soluble silica and calcium ions from 70S30C scaffolds induces an increase in osteoblast numbers as determined via the MTT assay. Scaffolds also support growth of endothelial cells on their surface and tube formation (characteristic of functional microvasculature) following 4 days in culture. This data supports the hypothesis that 70S30C bioactive glass scaffolds promote the differentiation of the 3 main cell types involved in vascularized bone regeneration.